find x = (-5/9)^14 × (-5/9)^5= (-5/9)^2x+3 ​

Question

find x = (-5/9)^14 × (-5/9)^5= (-5/9)^2x+3 ​

in progress 0
Cora 5 months 2021-12-13T02:43:58+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-12-13T02:45:19+00:00

    Answer:

    x=11

    Step-by-step explanation:

    (5/9)^14×(5/9)^5=(5/9)^2x+3

    take (5/9) as common

    so, (5/9)^14+5=(5/9)^2x3

    cancle (5/9) from both sides

    so, 14+5=2x3

    14+5+3=2x

    2x=22

    x=22/2

    x=11

    Mark me as BRAINALIST Please

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )